Deep infiltrative endometriosis. Contentious issues: pros and cons - Elena I. Rusina; Maria I. Yarmolinskaya; Valeriia O. Piankova (IP Berlin A.V., 2020)
Relevance.Deep infiltrative endometriosis (DIE) is a particular form of endometriosis with a more severe symptoms and dysfunction of the neighboring organs. Inspite of the fact that in recent years, much had been done to understand the pathogenesis of the disease and its associated symptoms; there are still several unresolved issues. Aim.To describe debated issues of pathogenesis and management of patients with DIE using current data. Materials and methods. Foreign and domestic scientific articles on this topic that is available in PubMed database and on Internet resources have been examined over the past 5 years. Results.The review consisted of a system analysis of data on the pathogenesis of pain, infertility, the choice of conservative or surgical treatment in dealing with specific problems of managing patients with DIE. Conclusion.Despite there are different options of managing and treating, most specialists agree that the treatment strategy should be based on the assumption that it is a chronic recurrent disease. The treatment choice should be personal depending on the severity of symptoms, dysfunction of the neighboring organs affected by endometriosis, such as the intestines, bladder, ureters, as well as the womans age and reproductive life plans. Depending on the clinical case, it is possible to use various regimens of conservative management. Surgical management planning should be highly balanced. A radical surgery with removing foci of endometriosis performed by an experienced surgeon in a specialized hospital in coupled with pharmacotherapy and assisted reproductive technologies increases the patients chances of pregnancy, a healthy childbearing. Subsequent combination therapy provides a long-term remission. Pregnancy and childbirth in patients with deep infiltrative endometriosis should be considered as a high risk condition for the severe complications.